The Influence of Perioperative Antibiotic Prophylaxis on Wound Infection and on the Colonization of Wound Drains in Patients After Correction of Craniosynostosis - Holle, Johannes; Finger, Tobias; Lugonja, Julia; Schmidt, Florian; Schaumann, Andreas; Gratopp, Alexander; Thomale, Ulrich-Wilhelm; von Bernuth, Horst; Schulz, Matthias (Frontiers in Pediatrics, 2021)
Objective Evidence for the duration of perioperative antibiotic prophylaxis (PAP) after the correction of craniosynostosis in children is scarce. We evaluated the necessary duration of PAP to ensure a minimal rate of postoperative wound infections. Methods In this monocentric, retrospective and prospective pilot study, two PAP protocols were compared. From August 2017 to May 2018 treatment group 1 (TG 1) was treated using the standard PAP protocol with at least 3 doses of antibiotics. Between May 2018 and March 2019, a shortened PAP with a single-shot administration was given to treatment group 2 (TG 2a and b). Endpoints of this study were wound infection rate, colonization rate of wound drains and the course of treatment reflected by clinical and laboratory data. Results A cohort of 187 children underwent craniosynostosis correction: 167 were treated according to protocols - 95 patients with at least three doses (TG 1) and 72 patients with a single-shot of cefuroxime (TG 2a). Baseline characteristics were similar for both groups. We could not detect significant differences, neither for wound infection rates (TG 1: 1.1%, TG 2a: 0.0%, p=0.38) nor for colonization rates of wound drains (TG 1: 4.8%, TG 2a: 10.5%, p=0.27). Conclusions Single-shot PAP had no adverse effects on the wound infection rate or the colonization rate of the wound drains compared to prolonged perioperative antibiotic prophylaxis. As a result, single-shot preoperative PAP is now applied to the majority craniosynostosis patients undergoing surgical correction in our unit.